The Irish Economy: Lessons for New Zealand? - Sarah Box (New Zealand Government, The Treasury, 1998)
This paper compares and contrasts the economies of Ireland and New Zealand. It attempts to identify important factors behind Ireland's recent strong growth, and seeks to derive 'lessons' for New Zealand. It is suggested that Ireland has benefited from its location, openness, macroeconomic stability, favourable demographics, educated population, wage moderation, foreign investment, European Union transfers, and luck! From a New Zealand viewpoint, the Irish experience reiterates the significance of quality investment, education and human capital, and macroeconomic stability and openness. But given the differences between the two countries, caution should be exercised in applying specific Irish policies in New Zealand.
Keywords: 330